1989
DOI: 10.1113/jphysiol.1989.sp017564
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent potassium channels in mouse Schwann cells.

Abstract: SUMMARY1. Ionic currents in Schwann cells cultured from enzymatically dissociated sciatic nerves of newborn mice were recorded by the whole-cell variation of the patch-clamp technique.2. In these cells only the voltage-dependent K+ currents were recorded. The K+ current was suppressed by quinine, 4-aminopyridine (4-AP) or tetraethylammonium (TEA), their half-suppression concentrations being 22 /tM, 0-3 mm and 15 mM, respectively.3. The peak amplitudes and density of the K+ currents in these Schwann cells incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 29 publications
6
43
0
Order By: Relevance
“…In Schwann cell cultures, the density of voltage-gated K+ channels increases rapidly during the first days of growth and the cell proliferation is delayed by K+ channel blockers (Konishi, 1989). Similar results were observed in Schwann cells from rabbit sciatic nerve explants (Chiu & Wilson, 1989).…”
Section: Discussionsupporting
confidence: 71%
“…In Schwann cell cultures, the density of voltage-gated K+ channels increases rapidly during the first days of growth and the cell proliferation is delayed by K+ channel blockers (Konishi, 1989). Similar results were observed in Schwann cells from rabbit sciatic nerve explants (Chiu & Wilson, 1989).…”
Section: Discussionsupporting
confidence: 71%
“…It cannot be assumed immediately that this value is the resting membrane potential (RMP) but it provides an estimate of the actual RMP (Push & Neher. 1987 (Shrager et al 1985), rabbits (Chiu et al 1984) and mice (Konishi, 1989a). In the same preparation as ours, Hoppe et al (1989) reported the presence of voltage-dependent and pH-sensitive K+ currents.…”
Section: Discussionsupporting
confidence: 63%
“…3B). The current-voltage relationships for these two currents are shown in Fig potential of -30 mV, displayed an inactivation process, called 'cumulative inactivation', similar to those described in molluscan nerve cell bodies (Aldrich, Getting & Thompson, 1979), in human T lymphocytes (DeCoursey, Chandy, Gupta & Cahalan, 1984) and in mouse Schwann cells cultured from sciatic nerves (Konishi, 1989a). In Fig.…”
Section: Membrane Currents Of Mouse Schwann Cells In Standard Conditionsmentioning
confidence: 59%
See 1 more Smart Citation
“…Cook, 1988). However, 4-AP has been found to block delayed rectifier currents in human T lymphocytes (DeCoursey, Chandy, Gupta & Cahalan, 1984), in mouse Schwann cells (Konishi, 1989) and in chick calcitonin cells (Kawa, 1988).…”
Section: Tail Currentmentioning
confidence: 99%